Affect and emotion : a new social science understanding - Wetherell, Margaret , 1954- (SAGE, 2012)
Emotion is an important topic in social science. This work - from a leading voice in the field - not only accessibly outlines the research from different fields, but is the first to pull it together to propose an agenda setting proposal for a definitive approach